Microstructural characteristics, electrical conductivity and mechanical properties of Cu matrix composites reinforced with dual-phase borides - Bo Li; Yimin Gao; Cong Li; Zhen Cao; Xingjuan Yao; Da Wu; Pucun Bai; Zhong Chen (Journal of Materials Research and Technology)
The effect of boride content on the microstructure, electrical conductivity, and mechanical properties of TiB2-MB2/Cu composites (M = Cr, Mo, and Zr) was systematically investigated. The composites were prepared via spark plasma sintering. The results indicated that the double borides were uniformly distributed in the Cu matrix without visible agglomeration, and excellent interfacial bonding was achieved between the borides and the Cu matrix. The electrical conductivity of the Cu composite with 5 wt% TiB2 and 15 wt% ZrB2 increased by 503 % compared to the Cu-20 wt% TiB2 composite. However, the hardness of the Cu composite with 5 wt% TiB2 and 15 wt% ZrB2 decreased by only 22 %. The wear resistance of the composites was significantly enhanced due to the synergistic effect of the dual-phase boride particles. The wear resistance of the Cu composite with 5 wt% TiB2 and 15 wt% ZrB2 was 4.12 times higher than that of the Cu-20 wt% TiB2 composite standard sample when tested under an applied load of 10 N. The worn surface of the composites exhibited minimal roughness. Therefore, the Cu matrix composites with dual-phase borides achieved desirable comprehensive performance in terms of electrical, mechanical, and tribological properties.